Ferrovias, nômades e exilados - Andrade, Carlos Roberto Monteiro de (Risco - Journal of Architecture and Urbanism, 2003)
What is theform of nomads territoriality? What distinguishes it from that of the exile? In searching for the answers to these questions, the paper discusses the interrelations between nomadism and the railway. This highlights the disciplinary dimension of this mean of transport which characterizes, among other features, the nomad's and exile's presence in the contemporary metropolis.